Surfactant Protein D in Respiratory and Non-Respiratory Diseases - Sorensen, Grith L. (Frontiers in Medicine, 2018)
Surfactant protein D (SP-D) is a multimeric collectin that is involved in innate immune defense and expressed in pulmonary, as well as non-pulmonary, epithelia. SP-D exerts anti-microbial effects and dampens inflammation through direct microbial interactions and modulation of host cell responses via a series of cellular receptors. However, low protein concentrations, genetic variation, biochemical modification, and proteolytic breakdown can induce decomposition of multimeric SP-D into low molecular weight (LMW) forms, which may induce pro-inflammatory SP-D signaling. Multimeric SP-D can decompose into trimeric SP-D, and this process, and total SP-D levels, are partly determined by variation within the SP-D gene, SFTPD. SP-D has been implicated in the development of respiratory diseases including respiratory distress syndrome, bronchopulmonary dysplasia, allergic asthma, and chronic obstructive pulmonary disease. Disease-induced breakdown or modifications of SP-D facilitate its systemic leakage from the lung, and circulatory SP-D is a promising biomarker for lung injury. Moreover, studies in preclinical animal models have demonstrated that local pulmonary treatment with recombinant SP-D is beneficial in these diseases. In recent years, SP-D has been shown to exert antimicrobial and anti-inflammatory effects in various non-pulmonary organs, and to have effects on lipid metabolism and pro-inflammatory effects in vessel walls, which enhance the risk of atherosclerosis. A common SFTPD polymorphism is associated with atherosclerosis and diabetes, and SP-D has been associated with metabolic disorders because of its effects in the endothelium and adipocytes and its obesity-dampening properties. This review summarizes and discusses the reported genetic associations of SP-D with disease and the clinical utility of circulating SP-D for respiratory disease prognosis. Moreover, basic research on the mechanistic links between SP-D and respiratory, cardiovascular, and metabolic diseases is summarized. Perspectives on the development of SP-D therapy are addressed.